2016
DOI: 10.1590/s1677-5538.ibju.2015.0491
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic features for quality of life after radical cystectomy and orthotopic neobladder

Abstract: Purpose:To analyse prognostic features on quality of life (QoL) following radical cystectomy and urinary diversion via orthotopic neobladder in a single-centre patient cohort.Materials and Methods:Postoperative QoL of 152 patients was assessed retrospectively using the validated QLQ-C30 questionnaire. Potential associations of patient's quality of life including pre-and intraoperative characteristics, surgeon experience, postoperative time course, adjuvant therapies, and functional outcome were defined a prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Formijne Jonkers et al (37) reported that 82% of patients who underwent creation of an intestinal stoma experienced one or more stomarelated complications within 1 year. Radical surgeries with creation of colostomy or urinary diversions deteriorate patients' organ functions, as well as patients' quality of life (33,(38)(39)(40). In our cohort, only three of 75 patients (4.0%) with boundary area involvement underwent colostomy or urinary diversion.…”
Section: Discussionmentioning
confidence: 74%
“…Formijne Jonkers et al (37) reported that 82% of patients who underwent creation of an intestinal stoma experienced one or more stomarelated complications within 1 year. Radical surgeries with creation of colostomy or urinary diversions deteriorate patients' organ functions, as well as patients' quality of life (33,(38)(39)(40). In our cohort, only three of 75 patients (4.0%) with boundary area involvement underwent colostomy or urinary diversion.…”
Section: Discussionmentioning
confidence: 74%
“…They also found that sexually active patients showed a significantly better QOL score compared with those being sexually inactive, also sexuality was the only independent factor related to QOL in the multivariate analysis [26]. Similarly Kretschmer et al [27] showed that a high erectile function score and nerve-sparing were associated with better QOL in patients with ONB after radical cystectomy.…”
Section: Sexual Functionmentioning
confidence: 85%
“…A current study which assessed postoperative quality of life of 152 patients with a median follow-up of 48 months revealed preoperative ECOG status, surgeon experience, and daytime incontinence as independent prognostic features of a good postoperative quality of life. 22 The impact of postoperative regimen on quality of life has not been examined so far. It is comprehensible that the postoperative management influences postoperative recovery in the short term and then influences long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%